THE STRETCHING EXERCISE INTERVENTION IN ADDITION TO MICRO WAVE DIATHERMI, TRANSCUTANEOUS NERVE STIMULATION ELECTRICAL AND MASSAGE DECREASE PAIN AMONG PATIENTS WITH CERVICAL SPONDYLOSIS - RINI UTAMI (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2013)
Objective : This research aimed to identifi addition intervention in stretchingexercise, micro wave diathermi, transcutaneous electrical nerve stimulation andmassage reduce pain spondylosis cervicalis. Method : This research is using pre testand post test control group design. Patients were randomised into two groups : theControl Group (CG) that use MWD, TENS and massage is 15 patients. The Experimental Group (EG) that MWD, TENS, massage and stretching exercise is 15patients too. Result : The result of CG test which using compare means with pairedsample t-test, p<0,05 (p=0,001) that mean the intervention in CG is having significantto reduce pain. In the result of EG test which using compare means with pairedsample t-test, p<0,05 (p=0,001) that mean the intervention in EG is having significantto reduce pain. The result test researcher using compare mean test with Independentsample t-test, p<0,05 (p=0,000), that means there are significant different between EGresult and CG result. In one tail hypothesis got result p<0,05, so it shows thatintervention in EG more effective significantly than CG in to reduce pain spondylosiscervicalis. Conclusion : Addition interevention in stretching exercise, micro wavediathermi, transcutaneous electrical nerve stimulation and masage reduce painspondylosis cervicalis.